Implementasi Ice Breaking Berbantuan Lagu ”Di Sini Teman di Sana Teman” untuk Meningkatkan Minat Belajar bagi Siswa Kelas 2 SDN Jatingaleh 01 - Kusumawardani, Erika Dwi; Rasiman, Rasiman; Supiyah, Supiyah; Rachmawati, Rivanna Citraning (MODELING: Jurnal Program Studi PGMI, 2024)
This research focuses on the implementation of ice breaking aided by the song "Disini Teman Disana Teman" to enhance learning interest among 2nd-grade students at SDN Jatingaleh 01. This study was conducted with the aim of implementing ice breaking using the song "Disini Teman Disana Teman" to enhance the learning interest of second-grade students at SD Negeri Jatingaleh 01. The research aimed to explore the implementation of ice breaking supported by the song "Disini Teman Disana Teman" to boost learning interest among second-grade students at SDN Jatingaleh 01. This qualitative research was carried out at one elementary school in Semarang, namely SD Negeri Jatingaleh 01. The subjects were second-grade students at SD Negeri Jatingaleh 01. Data collection techniques included observation, interviews, and documentation. The researcher analyzed the data using descriptive data analysis. The results indicate that the implementation of ice breaking has been conducted at SD Negeri Jatingaleh 01. Based on the research findings, it is evident that ice breaking has had a positive impact on children in their learning process. This is observed through several aspects: 1) Ice breaking helps build self-confidence, strengthens relationships among students, reduces awkwardness, and fosters a positive environment for further learning or collaboration. 2) Ice breaking alleviates boredom. 3) It engages the interest of second-grade students at SD Negeri Jatingaleh 01. 4) It enhances the effectiveness of learning. Ice breaking, facilitated by the song "Disini Teman Disana Teman," is conducted at the beginning of lessons to create an enjoyable learning atmosphere and foster camaraderie among students. The implementation of ice breaking has been perceived positively by the students.